Praktek Pembuatan Akta Jual Beli Hak Atas Tanah Yang Dilakukan Oleh Notaris Sebelum Berlakunya Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Based on the Government Regulation number 24 year 1997 on Land Registration that the authorized officer to certify the contract of sale is Pejabat Pentbuat Akta Tanah that is known as PPAT (not a public notary), but in reality there are many public notaries make the bond of sale certificate on land rightfulness to settle the transaction between the owner and the buyer. This is judicial normative research so that the ones being observed are the consecutive laws supported by empirical data. The data used in this research are taken from literary and field research. The field research was conducted in Sleman County, Bantul County, Gunung Kidul County and Yogyakarta Municipality. The field research data were abstracted from respondents with public notary background and resourceful experts. The method of purposive sampling is used in sampling respondent and resourceful experts. By looking into the result of the research, it is concluded that: 1. Public notary has the right to make the bond of sale certificate, with or without the payment being settled. 2. The bond of sale certificate on land rightfulness made by a public notary does not transfer the land rightfulness from an owner to a buyer.